Model Pembiasaan Karakter Kedisiplinan melalui Kegiatan Ekstrakulikuler Pramuka di MI Al-Muhsin Yogyakarta - Mizaniya Mizaniya; Muqowim Muqowim (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2020)
This research is motivated by the current era of strengthening character education is an important thing to do considering the number of loss of character education values currently very alarming. One of the characters that must be possessed by students as an effort in social problems is the character of discipline. The formulation of the problem in this study is how to model the discipline of disciplinary character through scout extracurricular activities in MI Al-Muhsin Yogyakarta. The purpose of this study was to determine the model of disciplinary character habituation through scout extracurricular activities at MI Al-Muhsin Yogyakarta. This research method is a type of descriptive research with a qualitative approach. Research subjects include the headmaster of madrasas, teachers, scoutmaster, and students. This research was conducted at MI Al-Muhsin Yogyakarta. When thhis research was conducted around March-April 2020. Data collection techniques used were observation, interviews, and documentation. Data collection tools used are audio, video and photo recording. Check the validity of the data by triangulating data and sources. While the data analysis used is data reduction, data presentation and data verification. The results showed that there was a model for disciplining character through the scout extracurricular activities at MI Al-Muhsin Yogyakarta through rewards and punishments applied. There is a relationship between scout extracurricular activities and disciplinary character. Evidence of the success of the Boy Scouts extracurricular activities in building disciplinary character at MI Al-Muhsin Yogyakarta, namely five minutes before the ceremony the students are ready and gathered by wearing the full boy scout uniform, students in an orderly manner paying front group contributions, and students are willing to pay fines and money Scoutmaster also pays if he does not order too. This research can add knowledge, experience as well as insights on the disciplinary character refraction model through scout extracurricular activities so that it can improve and be considered for other researchers, as prospective educators to enter the world of education.